When I miss you - Spelman, Cornelia; Parkinson, Kathy (Morton Grove, Ill. : Albert Whitman, 2004)
A young guinea pig describes situations that make him miss his parents, how it feels to miss them, and what he can do to feel better.
Booklist
Horn Book
1.4
K-3
K-3
Keywords: Guinea pigs -- Fiction; Loneliness -- Fiction; Parent and child -- Fiction; Guinea pigs -- Fiction; Loneliness -- Fiction; Parent-child relationship -- Fiction